Home School Guidelines for Fundamental Education, Case Study: Chiang Rai Province, Thailand - Unkong, Thidawan; Lamnaknet, Patcharida; Onaud, Alistra (Rajapark Journal, 2024)
This research aimed to study 1) the basic information about fundamental education management by families (homeschool): a case study in Chiang Rai Province; 2) the lessons learned about fundamental education management by families (homeschool): a case study in Chiang Rai Province; and 3) the development of guidelines for fundamental education management by families (homeschool): a case study in Chiang Rai Province. This research employed a combination of quantitative and qualitative methods. The population studied included families providing fundamental education. Primary Educational Service Area in Chiang Rai Province and experts. The instruments used for data collection were questionnaires and structured interview forms. The statistical analysis included percentages, means, standard deviation, and content analysis. The result indicated that fundamental education management by families (homeschooling) was at a high level. The lesson learned showed interesting points in homeschooling. One advantage is that family education organizers can create and modify curricula tailored to the aptitudes and interests of learners. Families also have more time to bond with each other. However, there are limitations: learners may lack social skills, have limited access to expensive learning materials, study managers might have less personal time, and there's a lack of government subsidy for lunches. The homeschool approach encompasses five aspects: 1) Principle; 2) Objective; 3) Input; 4) Process; and 5) Expected Results. The guideline of homeschooling for fundamental education aims to cultivate learners with three attributes: 1) Learners have educational standards based on national guidelines. 2) Learners receive education according to their interests, potential, and aptitude and 3) Students learn in an integrated way that aligns with their lifestyle and family.